Genomic data from Magellanic penguin ( Spheniscus magellanicus ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Magellanic penguin breeds in coastal Argentina, Chile and the Falkland Islands. Nests are built under bushes or in burrows, and they lay eggs in warm places when the temperature remains over 20. Magellanic penguins travel in large flocks when hunting for food. The International Union for Conservation of Nature (IUCN) classifies the Magellanic penguin as near threatened. We sequenced the genome of an adult Magellanic penguin from Chiloe Island, Chile (provided by Juan Bouzat) to a depth of approximately 171x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.2Gb, with the contig and scaffold N50 values of 40.48Kb and 12.09Mb respectively. We identified 16795 protein-coding genes. ...